2011
DOI: 10.1172/jci43964
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous collagen peptide activation of CD1d-restricted NKT cells ameliorates tissue-specific inflammation in mice

Abstract: IntroductionThe immune system responds to invading pathogens by recognizing their antigenic structures, while remaining unresponsive to self antigens. This simplified model, however, is challenged by the understanding that autoreactivity is a common feature of healthy organisms and a part of peripheral tolerance mechanisms. To generate animal models for autoimmune diseases, susceptible species are often immunized with self antigens. However, not all immunogenic self antigens have the capacity to provoke a path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 46 publications
(42 reference statements)
0
47
0
Order By: Relevance
“…However, due to difficulties in understanding the molecular basis of peptide recognition and the preponderance of lipid-reactivity among CD1d-restricted T cells, the issue of peptide-reactivity was largely put to rest. A more recent study reported CD1d-restricted recognition of a collagen-derived peptide by CD4 + T cells [102], but its molecular basis was unclear. Until the recent study by Girardi et al .…”
Section: Cd1dmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to difficulties in understanding the molecular basis of peptide recognition and the preponderance of lipid-reactivity among CD1d-restricted T cells, the issue of peptide-reactivity was largely put to rest. A more recent study reported CD1d-restricted recognition of a collagen-derived peptide by CD4 + T cells [102], but its molecular basis was unclear. Until the recent study by Girardi et al .…”
Section: Cd1dmentioning
confidence: 99%
“…Although the functions of peptide-reactive dNKT cells remain to be determined, it is striking that the CD1d peptide motif is contained within peptides derived from several viruses such as HIV [103], suggesting potential anti-viral functions. Additionally, studies with the CD1d-binding, collagen-derived peptide have provided evidence for potent immune modulatory activities of peptide-reactive, CD1d-restricted T cells [102]. …”
Section: Cd1dmentioning
confidence: 99%
“…SGL-S23 also suppressed histamine release, and more effectively so than α-GalCer or high dose IFN-. Finally, CIA suppression through NKT cell manipulation can be accomplished with nonglycolipid stimulation as shown by Liu et al (2011). Immunisation with murine CII induces a weaker responsethan heterologous collagen, characterised by multiple epitopes sharing a common motif, the strongest located at position 707-721.…”
Section: Manipulating Inkt Cells For Clinical Benefitmentioning
confidence: 99%
“…NKT cells are a subgroup of T-cells, which express the NK cell surface marker NK1.1 and a restricted TCR repertoire recognizing glycolipids and self-peptides presented by the major histocompatibility complex class 1-related glycoprotein CD1d (Fowlkes et al, 1987;Makino et al, 1995;Issazadeh-Navikas, 2012;Liu et al, 2011a). Besides being expressed on professional APCs a recent report has shown that CD1d is also expressed on epithelial cells in the human vagina (Kawana et al, 2008).…”
Section: Introductionmentioning
confidence: 99%